2023
DOI: 10.3847/1538-4357/acb267
|View full text |Cite
|
Sign up to set email alerts
|

Geoeffectiveness of Interplanetary Alfvén Waves. I. Magnetopause Magnetic Reconnection and Directly Driven Substorms

Abstract: In particular during the descending phase of the solar cycle, Alfvén waves in the high-speed solar wind streams are a major form of interplanetary disturbances. The fluctuating southward interplanetary magnetic field (IMF) of Alfvén waves has been suggested to induce geomagnetic activities through intermittent magnetic reconnection at the magnetopause. In this study, we provide in situ observational evidence for dayside magnetopause reconnection induced by such interplanetary Alfvén waves. Using multipoint con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 81 publications
4
29
0
Order By: Relevance
“…Tsurutani and Gonzalez (1987) and Tsurutani et al (2011) concluded that the major cause of geomagnetic activity during extended HILDCAA intervals, associated with high speed solar wind streams, is large amplitude Alfvén waves. Dai et al (2023) confirmed these findings in multiple events in corotating interaction region-driven geomagnetic storms. They noted that Alfvénic fluctuations in the solar wind associated with repetitive substorms contributed to the extended recovery phases of geomagnetic storms, and that such intervals were promptly followed by hundreds of nT increases in the AE and AU auroral electrojet indices within 10-20 minutes.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Tsurutani and Gonzalez (1987) and Tsurutani et al (2011) concluded that the major cause of geomagnetic activity during extended HILDCAA intervals, associated with high speed solar wind streams, is large amplitude Alfvén waves. Dai et al (2023) confirmed these findings in multiple events in corotating interaction region-driven geomagnetic storms. They noted that Alfvénic fluctuations in the solar wind associated with repetitive substorms contributed to the extended recovery phases of geomagnetic storms, and that such intervals were promptly followed by hundreds of nT increases in the AE and AU auroral electrojet indices within 10-20 minutes.…”
Section: Discussionsupporting
confidence: 67%
“…They noted that Alfvénic fluctuations in the solar wind associated with repetitive substorms contributed to the extended recovery phases of geomagnetic storms, and that such intervals were promptly followed by hundreds of nT increases in the AE and AU auroral electrojet indices within 10-20 minutes. Dai et al (2023) also presented a phenomenological model of strongly driven substorms, in which the increase of the AE index is linked to dayside reconnection mainly through the ionosphere (through enhanced two-cell convection) instead of the magnetotail, and suggested that this pattern is expected to be particularly viable and even dominant in the descending phase of the solar cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The average response of SME indicates that Alfvén waves have a general relation with moderate AE activities. As shown in the in situ observations in our accompanying Paper I (Dai et al 2023), the connection between Alfvén waves and AE increases is made possible by dayside magnetopause reconnection. The observations of the SME index suggest that Alfvén waves generally drive enhanced magnetosphere/ionosphere convection through transient magnetopause reconnection.…”
Section: Geomagnetic Responses To Interplanetary Alfvén Wavesmentioning
confidence: 59%
“…The energetic particle injections are commonly produced by storms and substorms (Dai et al., 2023; Han et al., 2023). The differences and similarities in ion flux levels, durations, and their association to AE and Dst indexes between storm‐time and isolated injections have been described in some previous works.…”
Section: Introductionmentioning
confidence: 99%